Analysis of the Impact of Yogyakarta International Airport (YIA) on the Financial Independence of Kulon Progo Regency - Srimaryani; Muhammad D (Formosa Journal of Social Sciences (FJSS), 2024)
This research aims to analyze the impact of YIA's existence on the financial independence of Kulon Progo Regency during three different time periods, namely the pre-COVID period (2018-2019), the Community Activity Restrictions (PPKM) period (2020), and the period entering the new normal era (2020). 2021-2022). The approach used in this research is through regional financial ratio analysis with a focus on taxes and levies. The research results show that the existence of YIA has a significant impact on tax and retribution revenues in Kulon Progo Regency. The results of this research provide a better understanding of the impact of YIA's existence on regional finances and can be used as a basis for making better policy decisions in the future